On-flow enzymatic inhibitor screening: The emerging success of liquid chromatography-based assays - De Oliveira, Pamella Christina Ortega; Lessa, Renato Côrrea; Ceroullo, Millena Santana; Wegermann, Camila Anchau; De Moraes, Marcela Cristina (Frontiers in Analytical Science, 2022)
Enzymes are targets commonly explored in screening assays aiming to discover new leads in the drug development process. Among the diverse assay models to identify new enzymatic inhibitors, on-flow assays based on liquid chromatography (LC) can be highlighted. In these approaches, the ligand-enzyme interaction can be examined by monitoring the catalytic activity or the affinity/retention. Most applications use the biological target immobilized in solid supports resulting in the acquisition of an immobilized enzymatic reactor (IMER). Coupling IMERs to LC or mass spectrometry (MS) systems allows monitoring enzyme activity online and studying binding events between target and ligands. On-flow screening assays present many advantages for the hit-to-lead process, such as the possibility of system automation, reusability, and high stability. This review covers articles from the last decade that combine the use of varied immobilization methods on different solid supports and several equipment setups in on-flow systems, emphasizing the performance and capacity of recognizing and identifying biologically active compounds in various matrices.